Guided meditation as an adjunct to enhance postoperative recovery after cardiac surgery: study protocol for a prospective randomized controlled feasibility trial - Senthil Packiasabapathy; Ammu T. Susheela; Ariel Mueller; Melissa Patxot; Doris-Vanessa Gasangwa; Brian O’Gara; Shahzad Shaefi; Edward R. Marcantonio; Gloria Y. Yeh; Balachundhar Subramaniam (Trials, 2019)
Abstract Background Cardiac surgical procedures are associated with postoperative neurological complications such as cognitive decline and delirium, which can complicate recovery and impair quality of life. Perioperative depression and anxiety may be associated with increased mortality after cardiac surgeries. Surgical prehabilitation is an emerging concept that includes preoperative interventions to potentially reduce postoperative complications. While most current prehabilitation interventions focus on optimizing physical health, mind–body interventions are an area of growing interest. Preoperative mind–body interventions such as Isha Kriya meditation, may hold significant potential to improve postsurgical outcomes. Methods This is a prospective, randomized controlled feasibility trial. A total of 40 adult patients undergoing cardiac surgery will be randomized to one of three study groups. Participants randomized to either of the two intervention groups will receive meditative intervention: (1) commencing two weeks before surgery; or (2) commencing only from the day after surgery. Meditative intervention will last for four weeks after the surgery in these groups. Participants in the third control group will receive the current standard of care with no meditative intervention. All participants will undergo assessments using neurocognitive, sleep, depression, anxiety, and pain questionnaires at various time points in the perioperative period. Blood samples will be collected at baseline, preoperatively, and postoperatively to assess for inflammatory biomarkers. The primary aim of this trial is to assess the feasibility of implementing a perioperative meditative intervention program. Other objectives include studying the effect of meditation on postoperative pain, sleep, psychological wellbeing, cognitive function, and delirium. These will be used to calculate effect size to design future studies. Discussion This study serves as the first step towards understanding the feasibility of implementing a mind–body intervention as a prehabilitative intervention to improve postoperative surgical outcomes after cardiac surgery. Trial registration Clinicaltrials.gov, NCT03198039. Registered on 23 June 2017.